Present and Past Helicobacter pylori Infection in Mexican School Children. Issue 1 (25th October 2013) - Mendoza, Eugenia; Camorlinga‐Ponce, Margarita; Perez‐Perez, Guillermo; Mera, Robertino; Vilchis, Jenny; Moran, Segundo; Rivera, Octavio; Coria, Rafael; Torres, Javier; Correa, Pelayo; Duque, Ximena
Abstract Background In developing countries, more than 50% of children have serological evidence of Helicobacter pylori infection. However, serological tests for H. pylori did not differentiate between active and past infection. The objectives of this study were to estimate the frequency of active and past H. pylori infection utilizing functional urea breath test (UBT) and serological tests and evaluate factors associated with the infection. Methods A total of 675 school children, 6–13 years of age, participated. UBT was performed to detect active H. pylori infection. Blood samples were obtained to determine iron status and Immunoglobulin G (IgG) responses to the H. pylori whole‐cell and to Cag A antigens by antigen‐specific enzyme‐linked immunosorbent assays. Weight, height, and sociodemographic characteristics were recorded. Results A total of 37.9% (95% Confidence Intervals (CI): 34.2–41.6) of school children had active or past H. pylori infection; of them, 73.8% (CI95% 68.4−79.2) were carrying CagA‐positive strain, 26.5% (CI95% 23.2–29.8) had active infection, and 11.4% (95%CI: 9.0–13.8) had evidence of past H. pylori infection. School children with iron deficiency and low height for age had higher risk of H. pylori infection: [OR to active or past infection was 2.30 (CI 95% 1.01–5.23) and to active infection it was 2.64 (CI 95% 1.09–6.44)] compared to school children with normal iron status and height for age or with normal iron status but low height for age or with iron deficiency and normal height for age. Conclusions The estimated prevalence of infection depends of the test utilized. Frequency of H. pylori infection and carrying CagA‐positive strains was high in this population. Malnutrition was associated with active H. pylori infection.